Comparative genomic analysis of Thermus provides insights into the evolutionary history of an incomplete denitrification pathway. Issue 2 (29th April 2022) - Jiao, Jian‐Yu; Lian, Zheng‐Han; Li, Meng‐Meng; Salam, Nimaichand; Zhou, En‐Min; Liu, Lan; Ming, Hong; Nie, Guoxing; Shu, Wensheng; Zhao, Guoping; Hedlund, Brian P.; Li, Wen‐Jun
Abstract: Biological denitrification is a crucial process in the nitrogen biogeochemical cycle, and Thermus has been reported to be a significant heterotrophic denitrifier in terrestrial geothermal environments. However, neither the denitrification potential nor the evolutionary history of denitrification genes in the genus Thermus or phylum Deinococcota is well understood. Here, we performed a comparative analysis of 23 Thermus genomes and identified denitrification genes in 15 Thermus  strains. We confirmed that Thermus harbors an incomplete denitrification pathway as none of the strains contain the nosZ gene. Ancestral character state reconstructions and phylogenetic analyses showed that narG, nirS, and norB genes were acquired by the last common ancestor of Thermales and were inherited vertically. In contrast, nirK of Thermales was acquired via two distinct horizontal gene transfers from Proteobacteria to the genus Caldithermus and from an unknown donor to the common ancestor of all known Thermus species except Thermus filiformis . This study expands our understanding of the genomic potential for incomplete denitrification in Thermus, revealing a largely vertical evolutionary history of the denitrification pathway in the Thermaceae, and supporting the important role for Thermus as an important heterotrophic denitrifier in geothermal environments. Impact statement: For decades, Thermus was always considered to be aerobic. However, recent studies have suggested that the denitrification abilities of Thermus species may be widely underestimated. In the present study, we used comparative genomic analysis to investigate the evolutionary history of the denitrification pathway in Thermus and other members of the phylum Deinococcota . We revealed incomplete denitrification pathways to be common in Thermus and showed they are inherited mostly vertically, which further supports the importance of Thermus as a significant denitrifier in hydrothermal environments.